Analisis Modal Intelektual Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Melalui Kinerja Perusahaan Sebagai Variabel Antara - Bayu Aji Kurniawan; muslichah muslichah (Jurnal Akuntansi dan Pajak, 2019)
This study examines the effect of intellectual capital and firm size on firm value with the company's financial performance as an intervening variable.. The sample used in this study is a food and beverage company that is listed on the Indonesia Stock Exchange (IDX) it the period 2014-2018. Data obtained by 65 samples. Data of this study is analyzed using path analysis. The results show that intellectual capital and firm size had a positive effect oncompany performance and firm value, and company performance mediate the effect of intellectual capital and firm size on firm value.